AN ECONOMIC ANALYSIS OF ADOPTION OF PRICE FORECASTS AND ITS IMPACT ON DECISION MAKING IN CHILLI FARMING - A. INDHUSHREE AND G. RAGHUNADHA REDDY (The Journal of Research ANGRAU, 2015)
The present study (2014-15) was conducted in Guntur district of Andhra Pradesh to analyse the factorsinfluencing adoption of price forecasts and to study the impact of price forecasts on decision making of the chillifarmers. The study revealed that education level, possession of communication assets by farmers, average annualincome of farmers and source of market intelligence to farmers were the significant factors influencing the adoption ofprice forecasts by farmers. Price forecast was found to have positive impact on farm decision making. The impact ofadoption of price forecasts was high in case of decision on quantity of chilli to sell followed by decision on storage ofproduce, allotting the area of land for chilli. The impact was also observed in case of decision regarding selection ofcrops time of harvesting and time of sowing.